Kedudukan Hukum Eks-Kreditor Pasca Debt to Equity Swap yang Dihomologasi dalam PKPU Kedua dan Kepailitan Debitor Akibat Pembatalan Perdamaian - Rahmawati, Reza (Jurnal Hukum & Pembangunan, 2026)
Debt to Equity Swap (DES) under a composition plan in Suspension of Debt Payment Obligations (PKPU) proceedings constitutes a restructuring mechanism that transforms the legal status of a Creditor into that of a shareholder upon homologation. Legal issues arise when The Debtor subsequently enters a Second PKPU due to newly incurred debts or is declared bankrupt following the annulment of the composition, while Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment does not expressly regulate the legal consequences of a DES under such circumstances. This normative legal research aims to analyze the legal standing and legal protection afforded to former Creditors after the implementation of DES. The findings indicate that DES constitutes an objective novation, extinguishing the original claim and replacing it with a corporate membership relationship. Consequently, in a Second PKPU, former Creditors may not reassert their previous claims unless a valid new debt arises. In bankruptcy resulting from annulment of composition, the DES remains valid, positioning former Creditors as subordinated shareholders, thereby shifting their legal protection from a Creditor's claim to shareholder rights within the company.